Imaging-guided Companion Theranostics: Ushering in A New Era of Personalized Cancer Care - Meng Li; Yumeng Wu; Jing Lin (Nano Biomedicine and Engineering)
Tumor heterogeneity has increasingly underscored the urgent need for personalized medicine, prompting the Food and Drug Administration (FDA) to approve in vitro companion diagnostics (CDx) for patient stratification. This evolving landscape has gradually transitioned towards imaging-based CDx, which is now further integrated with therapeutic modalities, culminating in the emergence of companion theranostics (CTx). In this review, we systematically elucidate the development of CTx and provide the first formal definition of this concept, thereby establishing a clear framework that distinguishes it from existing diagnostic approaches. We particularly emphasize the design principles underlying CTx by introducing activation strategies that leverage tumor active markers and treatment-activation mechanisms to enhance therapeutic precision. Finally, we address key challenges that remain, including the markers discovery, fine-tuning probes design, and regulatory approvals for clinical applications. We hope the insights shared in this review will contribute to the design of CTx for oncology, advancing personalized medicine.